Microsoft Excel and Google Form Training for Administrative Data Management of Hamlet Heads in Wedomartani - Aloysius Agus Subagyo; Asyahri Hadi Nasyuha; Wijang Widhiarso; Mesti Woro Mahatmi; Catur Setyono (Jurnal IPTEK Bagi Masyarakat, 2026)
The administration of hamlets at the grassroots level requires orderly data management and clear information presentation to support effective public services. Hamlet heads (Kepala Padukuhan) in Wedomartani Village still face limitations in processing administrative data and presenting information digitally, as recording activities largely rely on manual methods and paper-based forms. This community service activity aims to improve the competence of hamlet heads in administrative data processing and information visualization through the use of Microsoft Excel and Google Form. The activity was carried out through three stages, namely preparation, training implementation, and mentoring with evaluation, using participatory and learning by doing approaches. Data were collected through pre-test and post-test, direct observation, and a participant satisfaction questionnaire. The results showed an increase in the average participant mastery score from 37.2% in the pre-test to 81.6% in the post-test, an improvement of 44.4 points across the five trained competency aspects. Participants were able to process administrative data, create tables and simple charts in Microsoft Excel, and design digital forms with Google Form for community data collection. The activity also produced ready-to-use Excel and Google Form templates. It is concluded that practical and applicable training effectively strengthens the digital capacity of hamlet heads and supports more orderly, accurate, and efficient administrative governance.